Comparative Aspects of the Implementation of Pedagogical Management Models in General Education Schools, Gymnasiums and Lyceums (Journal of Educational Sciences, 2025)
The article presents the results of the analysis of various models of pedagogical management in general education schools, gymnasiums and lyceums in terms of comparison and identification. The need to organize effective pedagogical management in educational institutions is becoming more relevant due to the increasing requirements for the quality of modern education. In this regard, the authors of the article set a goal to identify the features of the models of pedagogical management of schools, gymnasiums, lyceums and substantiate their improvement in practice. During the study, the similarities and differences of management models in schools, gymnasiums and lyceums were comprehensively considered, and their impact on the quality of education and the effectiveness of students and teachers was assessed.As research methods, an expert survey was conducted and some modern methods of pedagogical management were considered. The article presents recommendations and approaches aimed at increasing the effectiveness of management models used in various educational institutions. The authors show ways to develop and improve pedagogical management at the school, gymnasium and lyceum levels, identify the main areas of increasing the impact and effectiveness of the management system on the learning process.The results of the study can serve as an aid to specialists in the field of education, including heads of educational institutions and teachers, in the effective use of management models in order to improve the learning process. The information presented in the article can serve as a basis for the future improvement of pedagogical management in the field of education.Key words: Pedagogical management, general education schools, gymnasiums, lyceums, management models, comparative research, educational management.